Leadership and strategy implementation in the Department of Home Affairs, Randburg - Mokgautsi, Boitshoko (My University, 2017)
The purpose of the research was to investigate leadership deficits within the Department of Home Affairs and its impact in the implementation of strategy. The research explored what the leadership is doing to promote and drive high performance, and also considered how leadership dynamics can be a barrier to effective strategy implementation. Investigation of these challenges was conducted at the local, regional and provincial level of the Department of Home Affairs. The research is based on qualitative research methodology. Interviews with staff and managers explained the development and implementation of strategies within the department. Interviews were face-to-face and semi-structured and allowed the researcher to clarify responses and to establish the roles played by the participants within the DHA. The nine participants interviewed play a central role in strategy implementation and organisational performance, and have direct or indirect contact with customers. In order to understand the leadership challenges and the effects on effective strategy implementation, a thorough interrogation of literature will be employed. The literature review further provided an understanding of the role of leadership in strategy implementation and assisted in identifying leadership deficits within the DHA and its impact on the implementation of strategy as well the role of leadership in strategy implementation in the DHA and its influence on performance. The study revealed that effective leadership can assist the organisation to structure interventions appropriately to respond strategically and effectively. Leaders must be able to persuasively communicate the strategy and how it will benefit employees, so that they are able to fully embrace and support it. The theoretical framework enabled the researcher to inform or explain the phenomenon under investigation. The literature review explained significant leadership theories, which included the transformational leadership theory, servant leadership, and strategic leadership theory. The conceptual framework of the study employed the 20-60-20 theory by Anunzio which is premised on creating and sustaining high performance, by engaging the workforce, and increasing staff’s commitment and job satisfaction. The study provided recommendations on policy considerations for the improvement of leadership and strategy implementation.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in the fulfilment of the requirements for the degree of Master of Management (in the field of Public Policy), University of the Witwatersrand, Johannesburg, 2017
Keywords: Leadership--South Africa; Public administration--South Africa--Management